El Excentrico, 1954-01-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
January 5, 1954 [5 de enero de 1954]. Anos 4, No. 5. Cover has a photo of Jorge Negrete in cowboy attire, smoking a cigarette. with headline, "El Charro Cantor." (transl: The Singing Horse Rider).